Analysis of Factors That Inhibition of Intention to Quit Smokingamong Outpatients Visiting Pulmonology Clinic at Dr. Zainoel Abidin Hospitals in Banda Aceh - Vera Nazhira Arifin; Ferlis Ferlis; Teuku Tahlil; Riza Septiani; Surna Lastri; Muhammad Muhammad (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Mortality rates in Indonesia are considered high with one of the contributing factors related to this condition is due to smoking behavior that is quite popular within society. Particularly, Aceh is one of the provinces with a high smoking prevalence as well as a high number of smokers. This study aimed to determine the factors that inhibit smoking cessation among outpatients who visit the pulmonology clinic at Dr. Zainoel Abidin Hospital in Banda Aceh. This study uses quantitative methods with a cross-sectional design. The population of this study is all patients who visit the pulmonology clinic at Dr. Zainoel Abidin Hospital in Banda Aceh, who are active smokers. The total sample is 65 respondents selected using the accidental sampling method. The results of the univariate analysis show that 56.92% of patients had the intention to stop smoking, 83.08% are active smokers for more than 5 years, 72.31% states about well the availability of cigarettes, 56.92% had low knowledge, 67.69% of patients had a negative attitude towards smoking cessation, 61.54% experiencing severe addiction in smoking, 70.77% smoking due to the influence of social environment. Bivariate analysis shows that there is a relationship between duration of smoking (p-value 0.029), smoking availability (p-value = 0.036), knowledge (p-value = 0.01), attitude (p-value = 0.03), cigarette addiction (p-value = 0,001), social environment (p-value = 0,004), family support (p-value = 0,007), information media (p-value = 0,011) with intention to stop smoking. This finding shows that the most influencing factor on intention to quit smoking is family support.